THE EFFECT OF CONSELLING USING VIDEO MEDIA OF KNOWLEDGE AND ATTITUDE OF YOUNG WOMEN ABOUT CERVICAL CANCER IN MADRASAH ALIYAH DARUL ULUM BANDA ACEH - Ulfa Farrah Lisa (JOURNAL OF HEALTHCARE TECHNOLOGY AND MEDICINE, 2015)
Cases of death due to cancer ranks second in the world after cardiovascular disease, which is about 13%. The prevalence of cancer in Indonesia is quite high, cervical cancer is second only to breast cancer, which is 17 per 100,000 women. cervical cancer should be wary as a teenager to do early detection and as the stock of knowledge to youth entering the age of marriage and so on. Information received since adolescence can lead to a positive attitude towards prevention and early detection of cervical cancer. video media can foster an attitude to analyze cause and effect and apply it in everyday life, through the medium of video teens understand and recall information/messages, help understanding and memory contents of the materials for young women who are weak in reading. This study aims to determine the effect of using video media on the extension of knowledge and attitudes about cervical cancer in young women in Madrasah Aliyah Darul Ulum Banda Aceh. This study uses a quasi-experimental with pretest-posttest design, done in Madrasah Aliyah Darul Ulum Banda Aceh on August 8, 2015. Total sample of 30 people with a total population of technique. Collecting data using questionnaires, data analysis using the Wilcoxon test. The study found that there is the effect of using video media on the extension of knowledge about cervical cancer in young women in Madrasah Aliyah Darul Ulum Banda Aceh with a value of p = 0.023, and there was no effect of the use of video media on the extension of knowledge and attitudes about cervical cancer girls in Madrasah Aliyah Darul Ulum Banda Aceh with a value of p = 0.129. Keywords: conselling, video media,knowledge, attitude, cervical cancer